The diagnosis and management of perniosis (chilblains) - H.F Jordaan (South African Family Practice)
Perniosis (chilblains) is an abnormal reaction to cold that occurs most frequently in women, children, and the elderly. Chilblains may be idiopathic and self-limited, or associated with systemic diseases. This article discusses the approach to the diagnosis and treatment perniosis and explains the concepts of acrocyanosis and erythrocyanosis.